2006
DOI: 10.1002/pmic.200500680
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of 2,3,7,8-tetrachlorodibenzo-p-dioxin-induced proteome alterations in 5L rat hepatoma cells using isotope-coded protein labels

Abstract: In an effort to contribute to a better understanding of the hepatic toxicity of the ubiquitous environmental pollutant and hepatocarcinogen 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD), a comprehensive quantitative proteome analysis was performed on 5L rat hepatoma cells exposed to 1 nM TCDD for 8 h. Changes in the abundances of individual protein species in TCDD-treated cells as compared to untreated cells were analysed using the nongel-based isotope-coded protein label (ICPL) method [Schmidt, A., Kellermann, J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
51
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(62 citation statements)
references
References 103 publications
11
51
0
Order By: Relevance
“…Out of these 168 nonredundant proteins, a mutant/control (H/L) protein ratio was calculated for 130 of them (all 130 proteins are listed in supplementary Table 3, and all peptide sequences for the identified proteins are listed in supplementary Table 4); for the remaining 38, this was not possible because of the absence of detected labeled peptides from either the control or the mutant sample. The minimum variation of H/L ratios associated to significant variation of protein expression was determined similarly to (34). The average of the CV (coefficient of variation) obtained for H/L ratios of all proteins for which at least two peptides were quantified was 11.1%.…”
Section: Sc-expressed Mirnas Affect Testicular Transcription-wementioning
confidence: 99%
“…Out of these 168 nonredundant proteins, a mutant/control (H/L) protein ratio was calculated for 130 of them (all 130 proteins are listed in supplementary Table 3, and all peptide sequences for the identified proteins are listed in supplementary Table 4); for the remaining 38, this was not possible because of the absence of detected labeled peptides from either the control or the mutant sample. The minimum variation of H/L ratios associated to significant variation of protein expression was determined similarly to (34). The average of the CV (coefficient of variation) obtained for H/L ratios of all proteins for which at least two peptides were quantified was 11.1%.…”
Section: Sc-expressed Mirnas Affect Testicular Transcription-wementioning
confidence: 99%
“…Moreover they have been successfully used in projects aiming at the identification of novel target genes of the AhR (14,35). We recently reported results of a proteomics study in which the effects of TCDD on 5L cells were investigated using an LC-based mass spectrometric approach, the so-called isotope-coded protein label (ICPL) method (36,37). In this study, we identified 89 protein species of various functional categories as up-or down-regulated by TCDD.…”
Section: Molecular and Cellular Proteomics 7:394 -410 2008mentioning
confidence: 99%
“…7,8 The separation of peptides by onedimensional nano reverse-phase liquid chromatography and their identification by matrix-assisted laser desorption/ionization time of flight mass spectrometry (MALDI-TOF/TOF), including the use of the GPS Explorer software for protein identification, were performed as described. 16 …”
Section: Reporter Gene Assaysmentioning
confidence: 99%